1989
DOI: 10.1073/pnas.86.24.10148
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of three gap junction proteins in developing and mature brain tissues.

Abstract: By using antibodies directed against gapjunction proteins of liver (connexins 26 and 32) and heart (connexin 43), we have localized immunoreactivity to specific cell types in frozen sections of adult rodent brains. Connexin 32 reactivity was found in oligodendrocytes and also in a few neurons, whereas reactivity to connexins 26 and 43 was localized to leptomeningeal cells, ependymal cells, and pineal gland. Immunoreactivity with antibodies to connexin 43 also occurred in astrocytes. Furthermore, during embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
335
3
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 478 publications
(371 citation statements)
references
References 27 publications
26
335
3
3
Order By: Relevance
“…0−4 per replica), which is similar to densities found in spinal cord, inferior olive, and suprachiasmatic nucleus (Rash et al, 1996(Rash et al, ,2001bNagy et al, 2004;and Rash, Nagy and Dudek, unpublished observations). Third, in contrast to purported abundance Cx32 in astrocytes (Alvarez-Maubecin et al, 2000), Cx32 was not found by FRIL in astrocytes at any age, paralleling observations in all other brain regions (Dermietzel et al, 1989;Nelles et al, 1996;Kunzelmann et al, 1997;Dermietzel, 1998;Rash et al, 2001b;Nagy et al, 2003b;Kamasawa et al, 2005). Fourth, consistent with our reports that detection of Cx26 and Cx32 is particularly sensitive to tissue fixation conditions (Li et al, 1997;Nagy et al, 2001Nagy et al, , 2003a, we found that the stronger 3.75% acrolein/2% formaldehyde fixative of AlvarezMaubecin (2000) applied under our conditions of immunohistochemistry abolished all labeling of Cx32 and Cx26 in brain parenchyma and greatly reduced Cx26 labeling in leptomeninges.…”
Section: How Abundant Are Neuronal Gap Junctions In Lc and Do They Csupporting
confidence: 73%
“…0−4 per replica), which is similar to densities found in spinal cord, inferior olive, and suprachiasmatic nucleus (Rash et al, 1996(Rash et al, ,2001bNagy et al, 2004;and Rash, Nagy and Dudek, unpublished observations). Third, in contrast to purported abundance Cx32 in astrocytes (Alvarez-Maubecin et al, 2000), Cx32 was not found by FRIL in astrocytes at any age, paralleling observations in all other brain regions (Dermietzel et al, 1989;Nelles et al, 1996;Kunzelmann et al, 1997;Dermietzel, 1998;Rash et al, 2001b;Nagy et al, 2003b;Kamasawa et al, 2005). Fourth, consistent with our reports that detection of Cx26 and Cx32 is particularly sensitive to tissue fixation conditions (Li et al, 1997;Nagy et al, 2001Nagy et al, , 2003a, we found that the stronger 3.75% acrolein/2% formaldehyde fixative of AlvarezMaubecin (2000) applied under our conditions of immunohistochemistry abolished all labeling of Cx32 and Cx26 in brain parenchyma and greatly reduced Cx26 labeling in leptomeninges.…”
Section: How Abundant Are Neuronal Gap Junctions In Lc and Do They Csupporting
confidence: 73%
“…Of the cloned connexins, Cx26 has been unique in that, with the possible exception of pinealocytes (22), it has consistently been found to be coexpressed with other connexins (2,13,14,23 Oocyte Preparation. Oocytes were prepared as described (25).…”
mentioning
confidence: 99%
“…However, whether CX26-mediated electrical coupling regulates the development and synapse formation of excitatory neurons in vivo remains unclear. In addition, although functional electrical coupling between excitatory neurons is largely eliminated after the first postnatal week, CX26 proteins remain abundantly present in excitatory neurons even at the mature stage (13,16). Therefore, the precise role of CX26 proteins in excitatory neurons after the disappearance of electrical coupling is unclear.…”
mentioning
confidence: 99%